A Professional Service Contract Without Early Ujrah: Fasid Ijarah and Ujrat al-Mitsl - Ichsanur Rizqi; Lathif Hanafir Rifqi; Amir Tajrid (Al-Amwal : Journal of Islamic Economic Law, 2026)
Purpose/Objectives – This study aims to analyze the legal position of professional service contracts without ujrah provisions at the beginning of the agreement from the perspective of sharia economic law, examine its classification as ijarah fasid and for, andte a contract reconstruction model in accordance with sharia principles and contemporary professional practices. Method – This study uses a qualitative approach with normative-juridical and socio-legal methods. Data were obtained through a study of classical and contemporary Ujrat al-Mitsl literature, an analysis of fatwas and legal documents, and a study of professional service contract practices. The analysis was carried out in a descriptive-analytical and interpretive manner. Result – The results of the study show that professional service contracts without ujrah are not necessarily canceled at first, but are classified as ijarah fasid because of the element of jahālah which has the potential to cause gharar. This study found that Ujrat al-Mitsl functions as a corrective instrument that determines rewards based on standards of market fairness and professional practice. In addition, a contract reconstruction model that integrates deferred ujrah, ujrah range, transparent calculation formula, and Ujrat al-Mitsl as a backup mechanism has been proven to be able to increase contractual certainty and fairness. Implication –This study emphasizes the flexibility of fiqh muamalah in responding to the dynamics of modern professional services and offers a more transparent, fair, and dispute-oriented framework in accordance with the sharia maqashid.